Analysis of horizontal cyclic bearing capacity of pile based on cyclic strain wedge finite element strip method. (December 2022) - Zhu, Wenbo; Dai, Guoliang; Xu, Jiang; Gao, Luchao; Gong, Weiming
Abstract: This paper proposes a cyclic strain wedge finite element strip model to analyze of the cyclic bearing characteristics of pile foundation. First, the strain wedge body is meshed by every soil element, which can assign the stress-strain relationship to each soil element of the wedge body. Then, the equivalent substitution stress‒strain relationship of each wedge layer can be obtained from the stress‒strain relationship of the soil element by the principle of the stress‒strain equivalent substitution method. It can truly reflect the stress-strain relationship of the soil to the stress-strain relationship of the wedge layer and the p - y curve. At the same time, the equivalent cyclic creep constitutive of soil is applied to the strain wedge finite element strip model for the cyclic bearing characteristics of the wedge layer and the cyclic p ‒ y curve. Finally, the cyclic strain wedge finite element strip model is verified by some tests. The results from the proposed method agree reasonably well with the measured results. It can provide a new method for analyzing the horizontal cyclic bearing characteristics of pile.